Study of Synergistic Effects of Heavy Toxic Metals on Aquatic Plants - Pathak, Vishal; Ritu Singh, Miss; Singh, S.K.; Pathak, Prabhat (Asian Journal of Chemistry, 2010)
Effects of heavy metals on biological systems have created interest following the increase in global use of these elements. These toxic heavy metals are being added continuously to the environment in large amounts. Synergistic effects of these elements. These toxic heavy metals are being added continuously to the environment in large amounts. Synergistic effects of these heavy toxic metals have been studied and concluded that a number of factors like species, strain, concentration and time period of exposure affect the interaction between metals. The possibility of complex formation of any two metals cannot be ignored.